THE SOCIOECONOMIC AND POLITICAL SITUATION IN JAVAKHETIA - MINASIAN, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2005)
On 10 March 2005, the Georgian parliament adopted a resolution on the Russian military bases deployed in the country. It noted that if Moscow does not adopt a decision be-fore 15 May on specific deadlines, acceptable to the Georgian side, for withdrawal of these troops, official Tbilisi will demand that the Russian Federation withdraw them before 1 January 2006. That is more, the Georgian side will spare no effort to ensure this is done. This document aroused an unequivocal reaction in Javakhetia (the Armenian name for Javakhk), where the 62nd Russian military base is stationed. As early as 13 March, a mass meeting of several thousand participants, un-precedented in the region’s history, was held in the town of Akhalkalaki, the region’s center, at which representatives of the local Armenian sociopolitical organizations protested the Georgian parliamentarians’ decision. What is more, they demanded that the country’s leadership take immediate measures to improve the socioeconomic and political situation in Javakhk and recognize the 1915 Armenian genocide that took place in Turkey.1 This meeting, which became a catalyst for several further events, has attracted the keen interest of political scientists and journalists both in the Southern Caucasus and beyond it to Javakhk once more. This region, which includes the Akhalkalaki and Ninotsminda districts, is located in the extreme southeast of Georgia and borders directly on Turkey and Armenia. The demographic specifics of this territory (Armenians constitute more than 95 percent of its population) have always colored the traditional view expressed by a number of researchers, political scientists, journalists, and politicians of the region as a potential conflict zone. In so doing, Georgian researchers evaluate the region’s conflict potential based on the possible separatist sentiments manifested by the local Armenian population. On the other hand, many other specialists, including Armenians, are primarily concerned about the situation in Javakhetia in light of the discrimination of the Armenian minority and protection of its rights to participate in sociopolitical, economic, and cultural life. At the same time, most foreign researchers view the region based on an analysis of the geopolitical problems associated with the South-ern Caucasus.2 The diverging views of Armenian and Georgian researchers (which are frequently diametrically opposed) are also revealed when light is shed on Javakhetia’s historical past. For example, Georgian scientists believe Samtskhe (Meskheti)to be one of the cradles of Georgian statehood,noting that the Armenian ethnic element did not appear here until the Russian-Turkish war of 1828-1829. However, Armenian historians claim that the region’s indigenous population consist-ed of Armenians from time immemorial, because this territory has always been part of historical Armenia. The demographic changes of the first quarter of the 19th century only restored the real picture, which had undergone changes due to the many centuries of Turkish dominion in Javakhk.